2015
DOI: 10.1002/jmri.24913
|View full text |Cite
|
Sign up to set email alerts
|

Support vector machine classification of brain metastasis and radiation necrosis based on texture analysis in MRI

Abstract: High classification accuracy (AUC > 0.9) was obtained using texture features and a support vector machine classifier in an approach based on conventional MRI to differentiate between brain metastasis and radiation necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
100
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(104 citation statements)
references
References 41 publications
4
100
0
Order By: Relevance
“…Larozza et al used a support vector machine classification and extracted 7 predictive features based upon texture analysis resulting in a sensitivity of 83% and a specificity of 82% to detect recurrent metastasis following radiosurgery (Larroza et al, 2015). In another study comprising 25 patients with brain metastasis, when using the five best features Tiwari et al observed a detection accuracy of 91% in the training set, resulting, however, in a diagnostic accuracy of only 50% in the validation set (Tiwari et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Larozza et al used a support vector machine classification and extracted 7 predictive features based upon texture analysis resulting in a sensitivity of 83% and a specificity of 82% to detect recurrent metastasis following radiosurgery (Larroza et al, 2015). In another study comprising 25 patients with brain metastasis, when using the five best features Tiwari et al observed a detection accuracy of 91% in the training set, resulting, however, in a diagnostic accuracy of only 50% in the validation set (Tiwari et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Textural feature analysis of inconclusive lesions on PET (Lohmann et al, 2017) and MR images (Larroza et al, 2015; Nardone et al, 2016; Pallavi et al, 2014; Tiwari et al, 2016) is another promising approach. It is based on the assumption that the microstructure of a process depends on the underlying pathology and is reflected in subtle differences in the radiological image that cannot be detected by means of human perception but can be made accessible by high-dimensional quantitative image analysis often referred to as “radiomics”.…”
Section: Introductionmentioning
confidence: 99%
“…GLCM is a gray-level spatial dependence matrix, consisting of values that show how often specific pairs of pixel value occur in a given spatial relationship in an image [12]. Recently the so-called large space conquest classification method was employed to investigate the textural parameters of brain MRI images, based on support vector machine , 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 or grading machine learning schemes [15]. The extraction of texture information can rely on several techniques, among which the Local Binary Pattern (LBP) method is getting more attention lately, as it provides promising results for a bunch of different applications [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Textural analysis could differentiate metastases from radiation necrosis after radiotherapy [15] In addition, there are at least two conceptually different texture analysis methods, the 2D and the 3D approaches. Mahmoud-Ghoneim et al showed that 3D method gives a better discrimination between necrosis and solid tumor as well as between edema and solid tumor [23].…”
Section: Introductionmentioning
confidence: 99%
“…brain lesion texture is correlated with presence and type of cancer cells. A recent study23 employed Haralick and wavelet texture features to distinguish radiation necrosis from metastatic brain tumor recurrence with a reported AUC of 94%. However, we believe that the results, reported on a per-slice basis, may have been affected by the classifier being contaminated by slices from the same patient being used both within the training as well as testing sets during classification.…”
Section: Resultsmentioning
confidence: 99%